Body Mass Index and Risk of Colorectal Cancer According to Fatty Acid Synthase Expression in the Nurses’ Health Study - Kuchiba, Aya (Oxford University Press, 2012)
Fatty acid synthase (FASN) plays an important role in energy metabolism of fatty acids and is overexpressed in some colon cancers. We investigated whether associations between body mass index (BMI) and risk of colorectal cancer varied according to FASN expression. During follow-up of 109 051 women in the ongoing prospective Nurses’ Health Study, a total of 1351 incident colon and rectal cancers were diagnosed between 1986 and 2004. We constructed tissue microarrays of the available resected tumor samples (n = 536), and FASN expression was analyzed by immunohistochemistry. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using Cox proportional hazards regression models. All statistical tests were two-sided. High BMI was associated with an increased risk of FASN-negative (no or weak expression) colorectal cancer compared with normal BMI (high BMI [≥30 kg/m(2)], ie, obese vs normal BMI [18.5–22.9 kg/m(2)], HR = 2.25, 95% CI = 1.49 to 3.40, P(trend) < .001) but not with FASN-positive (moderate to strong expression) colorectal cancer. A statistically significant heterogeneity in colorectal cancer risks was observed between FASN-negative and FASN-positive tumors (P(heterogeneity) = .033). The age-adjusted incidence rates for FASN-positive and FASN-negative colorectal cancers were 10.9 and 7.1, respectively, per 100 000 person-years. This molecular pathological epidemiology study supports a role of energy metabolism in colorectal cancer pathogenesis.